Love by the numbers : how to find great love or reignite the love you have through the power of numerology - McCants, Glynis, 1963- (Sourcebooks Casablanca, 2009)
The bestselling author of "Glynis Has Your Number" reveals the numerology of love. Using just a name and date of birth, readers can learn who they are destined to love, when to proceed with caution, and when to get serious.